Development of triethylamine detecting semiconductor sensor and to study its metrological description in technical and ecological safety - Abdurakhmonov Ergashboy; Muradova Zulfiya; Zikirov Salokhiddin (E3S Web of Conferences, 2024)
In this study, a semiconductor sensor was developed to detect triethanolamine. The influence of various factors on the metrological parameters of the developed sensor is investigated. Studies have shown that when using semiconductor films based on SnO2 and Fe2O3, the optimal temperature providing the maximum signal of the gas-sensitive material (GSM) relative to trimethylamine is 375 °C. At this temperature, it was observed that the signal value corresponding to the same concentration of triethylamine increased with an increase in the amount of iron oxide in gassensitive materials. The temperature of 375 ° C on the surface of the fuel was provided under the influence of a voltage applied to the sensor equal to 2.1 V. Therefore, subsequent experiments were carried out at a voltage value applied to the sensor, 2.1 V. The change in the resistance of the semiconductor sensor corresponding to different temperature values is explained by the difference in the adsorption of gases on the surface of fuels and lubricants and by different mechanisms of their interaction, which makes it possible to selectively determine triethylamine in the presence of other gases.